COLLECTIVE FLOW IN HEAVY-ION COLLISIONS FOR E b =0.25-1.15 GeV / NUCLEON - SRISAWAD, PORNRAD; ZHENG, YU-MING; YAN, YUPENG; KOBDAJ, CHINORAT; XING, YONG-ZHONG (Modern physics letters A, 2009)
The study of the various collective flows of nuclear matter is one of the main subjects in heavy ion physics. The interest in collective nuclear motion under extreme conditions, like high density and/or high temperature originates from the equation of state (EOS) of nuclear matter. We investigate the collective transverse flow in heavy ion collisions at incident energies of 0.25 A GeV to 1.15 A GeV for Au + Au system within the quantum molecular dynamical (QMD) model. Some preliminary results are given and discussed.